The Socialisation of the Impact of Smartphone Use on the Gumukmas Pekon Community - Septia Nagara, Erliza; Marselina Jupon, Rara; Damayanti, Alfina; Maseleno, Andino (SATKRIYA : Jurnal Pengabdian Kepada Masyarakat, 2023)
The proliferation of technological advancements in the contemporary digital era has significantly broadened the reach and influence of smartphone electronic media among adolescents. Smartphones primarily serve as a means of facilitating long-distance communication and accessing information through the internet. In addition to this, it has been observed that the proliferation of smartphones among adolescents who are now enrolled in educational institutions has not only yielded beneficial effects for the enhancement of their academic achievements, but also harbours the possibility of engendering a range of adverse consequences. As a consequence of this issue, the process of socialisation in the Gumukmas community has been primarily centred on the adverse effects associated with the utilisation of smartphones. This initiative seeks to provide educational resources to parents with children, enabling them to acquire knowledge on effective strategies for mitigating the potential negative effects of cellphones on their adolescent offspring.